Patient-centered care and patient satisfaction: Validating the patient-professional interaction questionnaire in China - Han, Tao; Li, Sisi; Li, Xueyuan; Yu, Chenhao; Li, Jiahui; Jing, Tiantian; Bai, Mayangzong; Fang, Yue; Qian, Kun; Li, Xiaoyan; Liang, Huigang; Zhang, Zhiruo (Frontiers in Public Health, 2022)
Objective: To introduce patient-centered approach in China and to relate it with Chinese patient satisfaction via validating the Chinese version of Patient-Professional Interaction Questionnaire (PPIQ-C). Design: This cross-sectional survey was conducted through face-to-face interviews from June to September in 2019. Participants rated their patient-centered care experience via the 16-item translated PPIQ, their experience of the received medical service, and their overall satisfaction. Setting: Kunshan Huaqiao People's Hospital in Jiangsu, China. Participants: A total of 230 participants (87 males and 143 females; 108 outpatients and 122 inpatients). Results: PPIQ-C exhibited excellent psychometric properties. A first-order and a second-order four-factor models were compared in terms of the model fit. Both models fitted the data well, with the second-order four-factor model providing slightly better fit (∆S-Bχ2 (2) = 0.8745, p < 0.001, CFI = 0.944, NFI = 0.922, RMSEA = 0.099). The overall reliability was excellent (Cronbach’s α = 0.974). In terms of patient satisfaction, process, treatment quality, and communication significantly predicted patient satisfaction, while the rest of medical perspectives did not (R2 = 0.427, F (6) = 24.887, p < 0.001). Additionally, PPIQ-C scores predicted patient satisfaction above and beyond the above-mentioned medical service perspectives (B = 0.595, SE = 0.207, p = 0.004; ∆R2 = 0.032, ∆F (∆df) = 11.834, p < 0.001). Finally, the constructive effect of PCC on patient satisfaction was stronger for departments of Pediatrics than Surgery. Conclusions: The Chinese version of the PPIQ scale (PPIQ-C) exhibited excellent internal consistency as well as theorized dimensionality. Patient-centered care (PCC), reflected by the PPIQ-C scores, predicted overall patient satisfaction above and beyond other medical service perspectives. Adopting PCC approach in appropriate situations will probably advance the development of performance evaluation systems in China, thus improving the overall health care and patient satisfaction.